2020
DOI: 10.2196/22060
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Public Knowledge About COVID-19, Trust in Information Sources, and Adherence to Social Distancing: Cross-Sectional Survey

Abstract: Background The success of behavioral interventions and policies designed to reduce the impact of the COVID-19 pandemic depends on how well individuals are informed about both the consequences of infection and the steps that should be taken to reduce the impact of the disease. Objective The aim of this study was to investigate associations between public knowledge about COVID-19, adherence to social distancing, and public trust in government information … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
194
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(232 citation statements)
references
References 31 publications
18
194
4
1
Order By: Relevance
“…In this sense, our results indicate significant differences in attitude toward information between people with high compliance and moderate compliance with rules. In line with the literature (Briscese et al, 2020;Fridman, Lucas, Henke, & Zigler, 2020;Bambini et al, 2020 ), our findings highlight the importance of implementing an effective public health communication campaign together with monitoring attitudes in the population to prevent potential disengagement effects. In planning practices for managing health crisis, policy makers should consider findings from both current and past pandemics.…”
Section: Discussionsupporting
confidence: 88%
“…In this sense, our results indicate significant differences in attitude toward information between people with high compliance and moderate compliance with rules. In line with the literature (Briscese et al, 2020;Fridman, Lucas, Henke, & Zigler, 2020;Bambini et al, 2020 ), our findings highlight the importance of implementing an effective public health communication campaign together with monitoring attitudes in the population to prevent potential disengagement effects. In planning practices for managing health crisis, policy makers should consider findings from both current and past pandemics.…”
Section: Discussionsupporting
confidence: 88%
“…Multiple studies have found WhatsApp and social media to be key information sources utilised in this pandemic, with citizens relying on them in preference to official public health websites [ 16 - 17 ]. However, social media has been known to spread false information [ 18 ], and lead to an underestimation of the severity of COVID-19 as compared to those who use government websites [ 19 - 20 ]. Our study supported the literature but suggested that although group messaging services such as WhatsApp were used by a significant proportion of our respondents (22¡2% of HCWs and 4¡1% of Non-HCWs), the majority used BBC News as their primary information source (37¡4% of HCWs and 66¡6%.…”
Section: Discussionmentioning
confidence: 99%
“…There is also public support for honest and accurate information during epidemics, even if that information is anxiety-provoking [ 26 ]. To ensure that this information is far-reaching, government and public health officials should utilise social media, infographics, and other forms of popular communication to their advantage [ 17 , 20 , 21 , 27 ] as well as ensuring the elderly generations are included in information campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of quality information online is unlikely to be a sufficient strategy to counter the influence of misinformation if digital health literacy is not accounted for. Messaging and debunking must be delivered on multiple trusted channels [34], consistent in content and style, and conveyed in local languages to ensure engagement with all communities [35]. Emerging evidence supports the idea that psychological inoculation-pre-emptively exposing people to small doses of misinformation techniques-can build resistance to false information across cultures [36].…”
Section: Principal Findingsmentioning
confidence: 99%